2002
DOI: 10.1017/s1466046602990058
|View full text |Cite
|
Sign up to set email alerts
|

ISO 14000 Standards and the US Construction Industry

Abstract: Construction activities generate a myriad of negative effects on the environment. ISO 14000, the series of environmental management standards released by the International Organization for Standardization in 1996, has been introduced as a tool that can aid in reducing these impacts. The implementation of these standards is focused on the establishment of an environmental management system (EMS) that can guide an organization toward achieving its own environmental goals. Certification for the ISO 14001 standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 0 publications
0
17
0
1
Order By: Relevance
“…On the contrary, the firm is enthusiastic to fulfill the environmental commitment and get competitive advantage against competitors in the construction industry [18]. Valdez and Chini (2002) USA, Construction firms Study based on single firm -The positive aspects of ISO 14001 is identified such as making commitments to environmental responsibility, improvement in environmental performance, increasing employee awareness, generating benefits like monetary savings and creating new marketing opportunities [19]. environment, enhancing public image and improving workers health and safety [3].…”
Section: Studies and Their Findings Based On Sample Of Firmsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, the firm is enthusiastic to fulfill the environmental commitment and get competitive advantage against competitors in the construction industry [18]. Valdez and Chini (2002) USA, Construction firms Study based on single firm -The positive aspects of ISO 14001 is identified such as making commitments to environmental responsibility, improvement in environmental performance, increasing employee awareness, generating benefits like monetary savings and creating new marketing opportunities [19]. environment, enhancing public image and improving workers health and safety [3].…”
Section: Studies and Their Findings Based On Sample Of Firmsmentioning
confidence: 99%
“…Since it was the first construction company to obtain certification in the US, auditor in charge of the process did not have previous construction experience or background. Another difficulty that has been experienced is maintaining people invested in the program and making sure that the program is consistently implemented in the entire company [19].…”
Section: Studies and Their Findings Based On Single Firmmentioning
confidence: 99%
“…About 90% of the construction companies had implemented or were about to implement an EMS in 2006 (Gluch et al, 2007). Valdez and Chini (2002) argue that the positive aspects of ISO 14000 certification in construction companies outweigh the negative aspects such as the costs of implementation. The positive environmental effects when companies introduce EMSs include improved environmental performance in the organisation, increased environmental awareness among employers and increased interest in environmental issues among subcontractors.…”
Section: Ems In the Construction Industrymentioning
confidence: 99%
“…The positive environmental effects when companies introduce EMSs include improved environmental performance in the organisation, increased environmental awareness among employers and increased interest in environmental issues among subcontractors. Increased government support and incentives to promote the adoption of EMSs in the construction industry has thus been recommended (Ofori et al, 2000;Valdez and Chini, 2002).…”
Section: Ems In the Construction Industrymentioning
confidence: 99%
“…Today, construction firms are motivated to implement the ISO 14001 EMS as a way of doing the following: (i) adapting to environmental legislation (Fundación Entorno, 2003); (ii) improving the public image of their firm (Turk, 2009); (iii) improving environmental performance (Fryxell and Szeto, 2002); (iv) increasing environmental awareness of employees (Fryxell et al, 2004;Turk, 2009;Matouq, 2000;Valdez and Chini, 2002) as well as to meet market demands.…”
Section: Introductionmentioning
confidence: 99%